Improved design and performance of the global rectenna system for wireless power transmission applications around 2.45 GHz - En-Naghma, Walid; Halaq, Hanan; El Ougli, Abdelghani (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This work proposes a new conception of the global microstrip rectenna system operating around 2.45 GHz. This improved rectenna system associates a receiving antenna with a rectifier circuit. This rectenna is printed on an FR4 substrate. The proposed antenna is a 1×4 microstrip antenna patch array with pentagonal patches using the defective ground structure method and operates with circular polarization. To show the effectiveness of this array, the results obtained by the computer simulation technology microwave studio (CST MWS) software prove that this array is good in terms of high gain, high directivity, high efficiency, wideband, small volume, and well-adaptation, and all these results are confirmed by another solver high-frequency structure simulator (HFSS). The improved rectifier is a microstrip rectifier that uses an HSMS2852 Schottky diode by using a series topology. The effectiveness of this rectifier is proved by the simulation results using advanced design system (ADS) software in terms of well-matching input impedance, high efficiency, and important output direct current (DC) voltage value. The proposed rectenna system is more efficient compared with the existing works and is very appropriate for several applications of wireless power transmission to power supply electronic instruments in various fields cleanly on our planet.